Global bioethics : issues of conscience for the twenty-first century - Green, Ronald Michael; Donovan, Aine; Jauss, Steven A. (Issues in biomedical ethics., 2008)
The ethics of medical care and biomedical research are rapidly becoming global. This volume gathers leading bioethicists to explore many new questions raised by the internationalization of medical care and biomedical research. Topics covered include, amongst others, the impact of globalization and the relation of religion to global bioethics. - ;Medical care and biomedical research are rapidly becoming global. Ethical questions that once arose only in the narrow context of the physician-patient relationship in relatively prosperous societies are now being raised across societies, cultures, and.